Quartz glass crucible for pulling up silicon single crystal and method for producing silicon single crystal using quartz glass crucible for pulling up silicon single crystal
During the single crystal silicon lifting process, the impurity concentration distribution and heating conditions on the inner surface of the quartz glass crucible are adjusted, and the crystallization in the in-plane direction is promoted, the peeling problem caused by uneven crystallization is solved, and the yield rate of single crystal silicon is improved.
Patent Information
- Application Number
- CN202380061084.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-24
- Filing Date
- 2023-08-03
- Publication Date
- 2025-04-04
AI Technical Summary
Prior Art During the single crystal silicon lifting process, the inner surface of the quartz glass crucible is unevenly crystallized, resulting in the crystallized part being easily peeled off, affecting the yield of the single crystal silicon.
By forming an impurity concentration distribution in a specific depth direction on the inner surface of the crucible and heating in the crystal lifting process, the crystallization speed in the in-plane direction is promoted to be faster than that in the depth direction, thereby forming a uniform and thin crystal layer.
The uniform crystallization of the inner surface of the crucible is achieved, the risk of peeling of the crystallized part is reduced, and the yield of single crystal silicon is improved.
Smart Images

Figure CN119768571A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a quartz glass crucible used in pulling single crystal silicon by the Czochralski method (CZ method) and a method for manufacturing the same. The present invention also relates to a method for manufacturing single crystal silicon using such a quartz glass crucible. Background Art
[0002] Most single crystal silicon that becomes the substrate material of semiconductor devices is manufactured by the CZ method. The CZ method is to melt polycrystalline silicon raw materials in a quartz glass crucible to generate silicon melt, immerse the seed crystal in the silicon melt, rotate the quartz glass crucible and the seed crystal, and slowly pull the seed crystal, thereby growing a larger single crystal at the bottom of the seed crystal. The CZ method can improve the yield of large-diameter single crystal silicon.
[0003] A quartz glass crucible (silica glass crucible) is a silica glass container that holds silicon melt in the single crystal silicon pulling process. Therefore, the quartz glass crucible is required to be durable enough to withstand long-term use without deforming at high temperatures above the melting point of silicon. In addition, high purity is required to prevent impurity contamination of single crystal silicon.
[0004] It is known that brown ring-shaped cristobalite crystals called brown rings grow on the inner surface of the quartz glass crucible in contact with the silicon melt during the pulling of single crystal silicon. If the brown rings peel off from the surface of the crucible and mix into the silicon melt, they may be transported to the solid-liquid interface by the convection of the melt and enter the single crystal. The peeling of cristobalite causes the dislocation of the single crystal silicon. Therefore, the inner surface of the crucible is actively crystallized by a crystallization promoter to prevent the peeling of crystal grains.
[0005] Regarding the method of strengthening the inner surface of the crucible by crystallization, for example, Patent Document 1 describes a method for manufacturing a highly durable crucible using calcium, strontium, and barium as crystallization promoters. Patent Document 2 describes a devitrification agent for a crucible with improved efficiency compared to the past. The devitrification agent includes barium and tantalum, tungsten, germanium, tin, or a combination of two or more of these, which is incorporated into the crucible during the construction process, applied to the surface of the final crucible, and / or added to the silicon melt used for crystal pulling.
[0006] Patent document 3 describes a surface-treated crucible with improved dislocation-free performance. The crucible includes a first and a second devitrification promoter distributed on the inner and outer surfaces of the sidewall formation of a body of vitreous silica, respectively. The first devitrification promoter is distributed in such a manner that when the semiconductor material melts in the crucible during crystal growth, a first layer of substantially devitrified silica is formed on the inner surface of the crucible in contact with the molten semiconductor material. In addition, the second devitrification promoter is distributed in such a manner that when the semiconductor material melts in the crucible during crystal growth, a second layer of substantially devitrified silica is formed on the outer surface of the crucible.
[0007] Patent document 4 describes a quartz glass crucible that can withstand a single crystal pulling process that takes a very long time, such as multiple pulling. The quartz glass crucible comprises: a crucible base body made of quartz glass and a first and a second coating film containing a crystallization promoter formed on the inner surface and the outer surface of the crucible base body, respectively. The first and the second coating films containing a crystallization promoter contain a polymer, and the crystallization promoter is a barium compound that is insoluble in water. Due to the action of the crystallization promoter, a crystal layer containing a collection of dome-shaped or columnar grains is formed on the surface layer of the inner surface and the outer surface of the crucible base body.
[0008] Patent document 5 describes a method for measuring impurity concentration distribution and a measuring fixture used in the method. The method comprises: repeatedly performing a process of bringing a specific area on the surface of a quartz crucible sample into contact with an etching solution to dissolve the surface and then recovering the etching solution, and measuring impurities contained in the recovered etching solution, thereby measuring the impurity concentration distribution from the crucible surface to the depth direction.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2012-211082
[0012] Patent Document 2: Japanese Patent Application No. 2019-509969
[0013] Patent Document 3: Japanese Patent Application Laid-Open No. 9-110590
[0014] Patent Document 4: Japanese Patent Application Publication No. 2020-200236
[0015] Patent Document 5: Japanese Patent Application Publication No. 2019-066262 Summary of the invention
[0016] Technical problem to be solved by the invention
[0017] As described above, the method of applying a crystallization promoter is effective in uniformly crystallizing the inner surface of the crucible. As a method of applying a crystallization promoter, there are brush-based coating, spray-based coating, and the like. In the method based on brush coating, uneven concentration in the in-plane direction is likely to occur, which easily produces uncrystallized parts in the coating area. In the method based on spray coating, the crystallization promoter sprayed in a mist will scatter, which easily produces uncrystallized parts near the boundary between the coating area and the uncoated area. Although the inner surface of the crucible will be melted due to contact with the silicon melt, the melting rate of the uncrystallized glass part will be faster than that of the crystallized part. Therefore, if pulling is performed, the crystallized part will remain and easily detach from the glass surface. If the grains detached from the inner surface of the crucible enter the silicon melt, it will cause dislocation of the single crystal silicon and cause a bad effect on the single crystal yield.
[0018] In order to prevent the non-crystallized part from remaining, it is effective to increase the concentration of the crystallization accelerator to promote crystallization. However, if the concentration of the crystallization accelerator is high, the crystallization speed will be faster not only in the in-plane direction but also in the depth direction, so that the crystal layer is excessive and the wall is thick. Because such a thick crystal layer is formed on the inner surface of the crucible, there is a problem that the crystal layer becomes easier to peel off.
[0019] In view of the above problems, the present invention aims to provide a quartz glass crucible and a method for manufacturing the same, which can form a uniform and thin crystal layer on the inner surface by heating in the crystal pulling process. In addition, the present invention aims to provide a method for manufacturing single crystal silicon using such a quartz glass crucible.
[0020] Solutions for solving technical problems
[0021] The inventors of the present application have conducted in-depth research on the crystallization mechanism of the inner surface of the crucible when a crystallization promoter is applied, and as a result, they have come to understand that by setting the impurity concentration in the depth direction near the inner surface of the crucible to a specific range, the crystallization of the inner surface due to heating during crystal pulling is faster in the in-plane direction than in the depth direction, thereby obtaining the present invention.
[0022] The present invention is based on such technical knowledge, and the quartz glass crucible for pulling single crystal silicon according to the present invention is characterized in that it comprises: a crucible base body comprising silica glass and a coating film containing a crystallization promoter formed on the inner surface of the crucible base body, wherein the Fe concentration contained in the first depth region at least 0.5 mm below the inner surface is higher than the Al concentration contained in the first depth region. In this way, with the quartz glass crucible according to the present invention, since the iron concentration contained in the depth region at least 0.5 mm from the inner surface of the crucible is higher than the aluminum concentration contained in the depth region, the crystallization speed in the in-plane direction of the inner surface can be accelerated. Therefore, even if the coating of the crystallization promoter occurs unevenly on the inner surface, the inner surface of the crucible is finally covered with a uniform crystal plane, so that the peeling of the crystallized part can be suppressed, thereby preventing the single crystal silicon pulled from the silicon melt in the crucible from being dislocated.
[0023] In the present invention, the Ca concentration in the first depth region is preferably higher than the Al concentration in the first depth region. Calcium has the same effect as iron, and since the crystallization of the inner surface of the crucible is easily extended inward, a uniform crystal surface can be formed on the inner surface of the crucible, thereby suppressing the peeling of the crystallized part.
[0024] In the present invention, the concentration of the metal element contained in the second depth region below 2 mm from the inner surface is lower than the concentration of the metal element contained in the third depth region above 2 mm and below 5 mm from the inner surface, and the metal element is preferably B, Mg or Cr. If boron, magnesium or chromium is present in the glass, the microstructure around its atoms will become a crystal structure with regular and correct arrangement. If the above-mentioned impurities exist from the inner surface to a certain depth, the crystallization speed in the depth direction from the inner surface to the outer surface side will become faster, so it is expected that there will be fewer impurities. In addition, it is possible to prevent the contamination of the silicon melt caused by the melting loss of the inner surface of the crucible.
[0025] In the present invention, the concentration of the crystallization accelerator in the coating film containing the crystallization accelerator is preferably 1.0×10 12 ~2.6×10 15 Atom / cm 2 If the concentration of the crystallization promoter is 2.6×10 15 Atom / cm 2 If the concentration of the crystallization accelerator is high, the crystallized particles will not be random, but will gradually crystallize in a form oriented in the depth direction. Therefore, the crystallization speed in the depth direction becomes faster, resulting in the consumption (diffusion) of the crystallization accelerator in this direction, making it difficult for the crystallization to diffuse in the in-plane direction. However, when the concentration of the crystallization accelerator is 2.6×10 15 Atom / cm 2In the following cases, crystallization in the depth direction can be suppressed and crystallization in the in-plane direction can be promoted.
[0026] When the quartz glass crucible based on the present invention is heat treated at 1580°C, the ratio of the crystallization rate in the in-plane direction to the crystallization rate in the depth direction is preferably 1.5 to 400. When the ratio of the crystallization rate in the in-plane direction to the crystallization rate in the depth direction is less than 1.5, the crystal layer will be too thick and the grains will easily peel off. In addition, when the ratio of the crystallization rate in the in-plane direction to the crystallization rate in the depth direction is greater than 400, a sufficient thickness of the crystal layer cannot be obtained, and there is a possibility that a portion where the crystal layer disappears due to the reaction with the silicon melt during pulling is generated. If the ratio of the crystallization rate in the in-plane direction to the crystallization rate in the depth direction is 1.5 to 400, such a problem can be prevented.
[0027] In the present invention, it is preferred that the heating time from room temperature to 1580°C for the heat treatment is 2.5 hours, the holding time at 1580°C is 10 hours, and the gas pressure during the heat treatment is 20 Torr. When the heat treatment is performed under such conditions, if the crystallization rate in the in-plane direction of the inner surface is greater than the crystallization rate in the depth direction, since crystallization in the in-plane direction can also be performed in the actual crystal pulling, a thin and uniform crystal layer can be uniformly formed on the inner surface of the crucible base.
[0028] In the present invention, it is preferred that the length of the in-plane direction of the crystallization extending from the inner surface after the heat treatment is 1 to 60 mm. When the length of the crystallization is shorter than 1 mm, an uncrystallized area may be generated due to unevenness of the crystallization promoter applied to the inner surface. When the length of the crystallization is longer than 60 mm, the crystallization will reach the upper end of the crucible opening, causing the peeled crystal layer caused by the excessive crystallization to fall into the silicon melt, thereby increasing the risk of dislocation.
[0029] In the present invention, it is preferred that the crystallization accelerator contained in the coating film containing the crystallization accelerator is Ba, and the concentration of Ba in the crystal layer formed after the heat treatment is less than 1 ppm.
[0030] In the present invention, it is preferably as follows: the crucible base has a cylindrical side wall portion, a bottom portion and a corner portion arranged between the side wall portion and the bottom portion, and in the inner surface of the crucible base, the area near the edge from the upper end of the edge to at least 20 mm below is an uncoated area of the crystallization promoter, and the coating film containing the crystallization promoter is formed on the entire inner surface except for the uncoated area.
[0031] Furthermore, the method for manufacturing a quartz glass crucible according to the present invention is characterized in that it comprises: a step of manufacturing a crucible base body containing silica glass; and a step of forming a coating film containing a crystallization accelerator on the inner surface of the crucible base body, wherein the step of manufacturing the crucible base body comprises: a step of sequentially putting natural quartz powder and synthetic quartz powder on the inner surface of a rotating mold to form a deposition layer of raw material powder; and an arc step of arc melting the deposition layer of the raw material powder from the inner side of the mold, wherein the arc step comprises: a first heating step; a second heating step, which is arc heating with a lower output and a longer time than the first heating step; and a third heating step, which is arc heating with a lower output and a longer time than the second heating step. In this case, the output of the first heating step is preferably 110% of the output of the second heating step, and the output of the third heating step is preferably 55% of the output of the second heating step. According to the present invention, a quartz glass crucible can be manufactured in which the crystallization rate in the in-plane direction of the inner surface of the crucible base body is faster than the crystallization rate in the depth direction.
[0032] In the present invention, it is preferred that the arc process includes: a transparent layer forming process, in which the accumulation layer of the raw material powder is vacuumed from the inside of the mold while arc melting is performed; and a bubble layer forming process, in which the vacuuming is stopped or the suction force is reduced while arc melting is performed, and the first heating process starts at the beginning of the transparent layer forming process and ends in the middle of the transparent layer forming process. Thus, the concentration of aluminum existing in the region from the inner surface of the crucible base to a depth of at least 0.5 mm can be reduced.
[0033] Furthermore, the method for producing single crystal silicon according to the present invention is characterized in that single crystal silicon is pulled up using the quartz glass crucible according to the present invention having the above-mentioned characteristics. According to the present invention, the production yield of single crystal silicon can be improved.
[0034] Effects of the Invention
[0035] According to the present invention, a quartz glass crucible and a method for manufacturing the same can be provided, which can form a uniform and thin crystal layer on the inner surface by heating in a crystal pulling process. In addition, according to the present invention, a method for manufacturing single crystal silicon can be provided, which can perform a long crystal growth process by using such a quartz glass crucible. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a schematic perspective view showing the structure of a quartz glass crucible according to an embodiment of the present invention.
[0037] Figure 2 yes Figure 1 A schematic side cross-sectional view of a quartz glass crucible is shown.
[0038] Figure 3 Schematic diagram for explaining the distribution of metal impurities in the depth direction from the inner surface of the crucible base.
[0039] Figure 4 Schematic diagram showing a method for producing a quartz glass crucible by rotational molding.
[0040] Figure 5 This is a diagram for explaining a method for producing a silicon single crystal (single crystal pulling step) using a quartz glass crucible according to the present embodiment, and is a schematic cross-sectional view showing the structure of a single crystal pulling apparatus. DETAILED DESCRIPTION
[0041] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings.
[0042] Figure 1 1 is a schematic perspective view showing the structure of a quartz glass crucible according to an embodiment of the present invention. Figure 2 yes Figure 1 A schematic side cross-sectional view of a quartz glass crucible is shown.
[0043] like Figure 1 and Figure 2 As shown, the quartz glass crucible 1 is a silica glass container for holding silicon melt, and has a cylindrical side wall portion 10a, a bottom 10b provided below the side wall portion 10a, and a corner portion 10c provided between the side wall portion 10a and the bottom portion 10b. The bottom portion 10b is preferably a so-called round bottom that is gently curved, but may also be a so-called flat bottom. The corner portion 10c is a portion having a greater curvature than the bottom portion 10b. The boundary position between the side wall portion 10a and the corner portion 10c and the boundary position between the bottom portion 10b and the corner portion 10c are positions where the curvature changes from a small curvature to a large curvature.
[0044] The caliber (diameter) of the quartz glass crucible 1 varies depending on the diameter of the single crystal silicon ingot pulled out from the silicon melt, but is 18 inches (about 450 mm) or more, preferably 22 inches (about 560 mm) or more, and particularly preferably 32 inches (about 800 mm) or more. The reason is that such a large crucible is used to pull large single crystal silicon ingots with a diameter of 300 mm or more, and it is required that the quality of the single crystal will not be affected even if it is used for a long time.
[0045] The wall thickness of the crucible slightly varies depending on the location, but preferably the wall thickness of the side wall 10a of a crucible larger than 18 inches is 6 mm or more, the wall thickness of the side wall 10a of a crucible larger than 22 inches is 7 mm or more, and the wall thickness of the side wall 10a of a crucible larger than 32 inches is 10 mm or more. This allows a large amount of silicon melt to be stably maintained at a high temperature. The wall thickness of the crucible is preferably thickest at the corner 10c, and the side wall 10a and the bottom 10b are thinner than the corner 10c.
[0046] like Figure 2 As shown, the quartz glass crucible 1 includes a crucible base 10 made of silica glass and a coating film 13 containing a crystallization accelerator formed on the inner surface 10i of the crucible base 10. The crucible base 10 is mainly a double-layer structure, and has a transparent layer 11 (bubble-free layer) containing no bubbles and a bubble layer 12 (opaque layer) containing a plurality of fine bubbles, and the coating film 13 containing a crystallization accelerator is provided on the inner side of the transparent layer 11.
[0047] The transparent layer 11 is a glass layer constituting the inner surface 10i of the crucible base 10 in contact with the silicon melt, and is provided to prevent the yield of the single crystal silicon from decreasing due to bubbles in the silica glass. The inner surface 10i of the crucible is melted due to the reaction with the silicon melt, so the bubbles near the inner surface of the crucible cannot be sealed in the silica glass, and there is a possibility that the bubbles will burst due to thermal expansion, resulting in the peeling of the crucible fragments (silicon dioxide fragments). When the crucible fragments released into the silicon melt are transported to the growth interface of the single crystal silicon by the convection of the melt and are incorporated into the single crystal silicon, it becomes a cause of dislocation of the single crystal silicon. In addition, when the bubbles released into the silicon melt float up and reach the solid-liquid interface and are incorporated into the single crystal, it becomes a cause of pinholes in the single crystal silicon.
[0048] The transparent layer 11 does not contain bubbles, which means that the bubble content and bubble size are such that the single crystal rate is not reduced by bubbles. The bubble content is, for example, 0.1 vol% or less, and the bubble diameter is, for example, 100 μm or less.
[0049] The thickness of the transparent layer 11 is preferably 0.5 to 10 mm, and is set to an appropriate thickness at each part of the crucible so that the transparent layer 11 does not completely disappear due to melting loss in the crystal pulling process, thereby exposing the bubble layer 12. The transparent layer 11 is preferably provided on the entire crucible from the side wall portion 10a to the bottom 10b of the crucible, but the transparent layer 11 may be omitted at the upper end of the crucible that does not contact the silicon melt.
[0050] The bubble content and the diameter of the bubble in the transparent layer 11 can be measured in a non-destructive manner using an optical detection mechanism. The optical detection mechanism is equipped with a light receiving device that receives the transmitted light or reflected light of the light irradiated to the crucible. The light receiving device can use a digital camera including an optical lens and an imaging element. As the irradiation light, in addition to visible light, ultraviolet light and infrared light, X-rays or laser light can also be used. The measurement results obtained by the optical detection mechanism are input to an image processing device to calculate the diameter of the bubble and the bubble content per unit volume.
[0051] The bubble layer 12 is a main glass layer of the crucible base 10 located outside the transparent layer 11, and is provided to improve the heat preservation of the silicon melt in the crucible and to disperse the radiation heat from the heater of the single crystal pulling device so as to heat the silicon melt in the crucible as uniformly as possible. Therefore, the bubble layer 12 is provided on the entire crucible from the side wall portion 10a to the bottom 10b. The thickness of the bubble layer 12 is approximately equal to the value obtained by subtracting the thickness of the transparent layer 11 from the thickness of the crucible base 10, and varies depending on the location of the crucible.
[0052] The bubble content of the bubble layer 12 is higher than that of the transparent layer 11, and is preferably greater than 0.1vol% and less than 5vol%. The reason is that if the bubble content of the bubble layer 12 is less than 0.1vol%, the heat preservation function required of the bubble layer 12 cannot be exerted. In addition, the reason is that when the bubble content of the bubble layer 12 exceeds 5vol%, there is a possibility that the crucible is deformed due to the thermal expansion of the bubbles, resulting in a decrease in the single crystal yield, and the thermal conductivity becomes insufficient. From the perspective of the balance between thermal insulation and thermal conductivity, the bubble content of the bubble layer 12 is particularly preferably 1 to 4vol%. In addition, the bubble content is a value obtained by measuring the crucible before use under room temperature. The bubble content of the bubble layer 12 can be obtained, for example, by measuring the specific gravity of an opaque silica glass piece cut from the crucible (Archimedes method).
[0053] In order to prevent contamination of the silicon melt, it is desirable that the silica glass constituting the inner side (innermost surface layer) of the transparent layer 11 is of high purity. Therefore, the crucible base 10 preferably has a double-layer structure of a synthetic silica glass layer (synthetic layer) formed by synthetic quartz powder and a natural silica glass layer (natural layer) formed by natural quartz powder. Synthetic quartz powder can be manufactured by gas phase oxidation of silicon tetrachloride (SiCl4) (dry synthesis method) or hydrolysis of silicon alkoxide (sol-gel method). In addition, natural quartz powder can be manufactured by crushing a natural mineral with α-quartz as the main component into granules.
[0054] The double-layer structure of the synthetic silica glass layer and the natural silica glass layer can be manufactured as follows: natural quartz powder is deposited along the inner surface of a crucible manufacturing mold, synthetic quartz powder is deposited thereon, and these raw quartz powders are melted by using the Joule heat obtained by arc discharge. In the arc melting process, bubbles are removed by strongly vacuuming the outer side of the raw quartz powder deposition layer to form a transparent layer 11, and the bubble layer 12 is formed by stopping or weakening the vacuuming. Therefore, the boundary surface between the synthetic silica glass layer and the natural silica glass layer may not be consistent with the boundary surface between the transparent layer 11 and the bubble layer 12, but the synthetic silica glass layer is preferably thick enough not to completely disappear due to the melting loss of the inner surface of the crucible in the single crystal pulling process, like the transparent layer 11.
[0055] The quartz glass crucible 1 of the present embodiment has a structure in which the inner surface 10i of the crucible base 10 is covered with a coating film 13 containing a crystallization promoter. The crystallization promoter is responsible for promoting the crystallization of the inner surface 10i of the crucible base 10 in the single crystal pulling process. The crystallization promoter is preferably barium (Ba) or strontium (Sr) of the 2a group element, and barium is particularly preferred. The reason is that barium has a smaller segregation coefficient than silicon, is stable at room temperature and is easy to handle. In addition, barium also has the following advantages: the crystallization rate does not decay with crystallization, and it promotes oriented growth more strongly than other elements.
[0056] The coating film 13 containing the crystallization accelerator is preferably formed on the entire inner surface 10i of the crucible base 10 except for the edge vicinity region from the upper end of the edge to at least 20 mm below. The reason for excluding the edge vicinity region is that the edge vicinity is not in contact with the silicon melt and does not necessarily need to be crystallized, and the edge vicinity is easily peeled off during crystallization, and the crystal grains mixed into the silicon melt become the cause of dislocation of the single crystal silicon.
[0057] The concentration of the crystallization accelerator contained in the coating film 13 containing the crystallization accelerator is preferably 1.0×10 12 ~2.6×10 15 Atom / cm 2 If the concentration of the crystallization promoter is 2.6×10 15 Atom / cm 2 If the concentration of the crystallization accelerator is higher, the orientation of the crystallized particles will not be random, but will gradually crystallize in a form oriented in the depth direction, so the crystallization speed in the depth direction becomes faster, resulting in the consumption (diffusion) of the crystallization accelerator in this direction, and thus it becomes difficult for the crystallization to diffuse in the in-plane direction. However, when the concentration of the crystallization accelerator is relatively low, the crystallization in the depth direction of the inner surface 10i of the crucible base 10 can be suppressed and the crystallization in the in-plane direction can be promoted. Therefore, the uniform crystallization of the inner surface 10i of the crucible base 10 can be achieved.
[0058] The thickness of the coating film 13 containing a crystallization accelerator is not particularly limited, but is preferably 0.1 to 50 μm, and particularly preferably 1 to 20 μm. The reason is that if the thickness of the coating film 13 containing a crystallization accelerator is too thin, the peel strength of the coating film 13 containing a crystallization accelerator is weak, and the crystallization becomes uneven due to the peeling of the coating film 13 containing a crystallization accelerator. If the coating film 13 containing a crystallization accelerator is too thick, the peel strength will also decrease, and the crystallization becomes uneven.
[0059] In order to make the inner surface of the crucible crystallize as uniformly and thinly as possible through heating in the crystal pulling process, the crystallization rate of the crystal layer in the in-plane direction needs to be faster than the crystallization rate in the depth direction. In particular, the ratio of the crystallization rate in the in-plane direction to the crystallization rate in the depth direction is preferably 1.5 to 400. In the case where the ratio of the crystallization rate in the in-plane direction to the crystallization rate in the depth direction is less than 1.5, the crystal layer will be too thick and the grains will be easily peeled off. In addition, in the case where the ratio of the crystallization rate in the in-plane direction to the crystallization rate in the depth direction is greater than 400, the sufficient thickness of the crystal layer cannot be obtained, and there is a possibility that the crystal layer disappears due to the reaction with the silicon melt during pulling.
[0060] Figure 3 Schematic diagram for explaining the distribution of metal impurities in the depth direction from the inner surface 10 i of the crucible base 10 .
[0061] like Figure 3 As shown in FIG. 1 , since the crystallization rate in the in-plane direction of the inner surface 10i of the crucible base 10 is set to be greater than that in the depth direction, the concentration of aluminum (Al) contained in the extreme surface portion of the crucible base 10 is preferably lower than the concentrations of iron (Fe) and calcium (Ca) contained in the extreme surface portion. Specifically, the concentration of Al contained in the depth region D1 (first depth region) from the inner surface 10i of the crucible base 10 to at least 0.5 mm is preferably lower than the concentration of Fe contained in the depth region D1. Furthermore, the concentration of Al contained in the depth region D1 from the inner surface 10i of the crucible base 10 to at least 0.5 mm is preferably lower than the concentration of Ca contained in the depth region D1.
[0062] Al exists in silica glass (quartz glass) as an anion (Al-) and adsorbs cations. Therefore, if Al exists in the glass, the diffusion of the crystallization promoter is inhibited, and the crystallization rate is slowed down. However, Fe and Ca do not capture the crystallization promoter, thereby promoting crystallization. Therefore, if Fe and Ca are present in a higher concentration than Al, it becomes easy to expand crystallization in the in-plane direction. In addition, by reducing the Al concentration of the inner surface 10i of the crucible base 10, the viscosity of the glass deeper than the crystal layer is prevented from decreasing, and the risk of peeling of the crystal layer due to deformation can be reduced.
[0063] Although Fe and Ca on the inner surface 10i of the crucible base 10 may cause impurity contamination of the single crystal silicon, as long as they are extremely small, they become the starting point of crystallization of the inner surface 10i, and have the effect of making the crystallization easily spread in the in-plane direction. In the present invention, the Al content of the inner surface 10i of the crucible base 10 is less than that of Fe and Ca. If Al exists more on the inner surface 10i, the effect of Fe and Ca will be weakened by the effect of Al, making it difficult for the crystallization of the inner surface 10i to proceed in the in-plane direction. However, since the concentration of Al is lower than that of Fe and Ca, it is possible to promote the crystallization of the inner surface 10i in the in-plane direction.
[0064] The details will be described later. Such a concentration balance of Al, Fe and Ca can be achieved as follows: synthetic quartz powder with a low Al concentration is used as the raw material of the inner surface 10i of the crucible base 10, and low-output arc discharge is performed for a long time at the end of the arc melting of the raw material powder. If the low-output arc time is too short, the change in the concentration of Fe and Ca on the inner surface 10i is not observed, and if the low-output arc time is too long, the impurity concentration on the inner surface 10i will become too high, so it is necessary to adjust the arc time appropriately. In this way, by performing a low-output arc, the concentration of Fe and Ca can be made higher than that of Al. Moreover, it is preferred to make the arc output high in the formation process of the initial transparent layer 11 of arc melting. In this way, the concentration of aluminum present in the region from the inner surface 10i of the crucible base 10 to a depth of at least 0.5 mm can be reduced.
[0065] In the present embodiment, the concentration of boron (B) contained in the depth region D2 (second depth region) from the inner surface 10i of the crucible base 10 to 2 mm or less is preferably lower than the concentration of B contained in the depth region D3 (third depth region) from the inner surface 10i to 2 mm or more and 5 mm or less. The same is true for magnesium (Mg) and chromium (Cr). If B, Mg and Cr are present in the glass, the microstructure around the atoms will become a crystal structure with regular and correct arrangement. Therefore, if there are more of the above impurities in the depth region D2 from the inner surface 10i of the crucible base 10 to 2 mm or less, the crystallization from the inner surface 10i to the depth direction will become faster, and it will become difficult to promote the crystallization of the inner surface 10i in the in-plane direction. However, if there are fewer impurities in the depth region D2 from the inner surface 10i to 2 mm or less, it is possible to suppress the crystallization from the inner surface 10i to the depth direction and promote the crystallization in the in-plane direction. Furthermore, it is possible to prevent the silicon melt from being contaminated by impurities due to the melting loss of the inner surface 10 i of the crucible base 10 .
[0066] Based on the quartz glass crucible of this embodiment, when heat-treated at 1500°C to 1600°C, the crystallization rate in the in-plane direction of the inner surface of the crucible is faster than the crystallization rate in the depth direction, so that the crystallization in the in-plane direction of the inner surface of the crucible can be promoted in the crystal pulling process. As heat treatment conditions, the temperature is raised from room temperature to 1580°C for 2.5 hours and then maintained at 1580°C for 10 hours. When the gas pressure is 20 Torr, the ratio of the crystallization rate in the in-plane direction of the inner surface of the crucible after heat treatment to the crystallization rate in the depth direction is preferably 1.5 to 400.
[0067] The length of the in-plane direction of the crystallization diffused on the inner surface after the heat treatment is preferably 1 to 60 mm. When the length of the crystallization in the in-plane direction is shorter than 1 mm, the crystallization promoter coated on the inner surface is prone to produce non-crystallized parts when it is uneven. When the length of the crystallization in the in-plane direction is longer than 60 mm, the crystallization will reach the upper end of the crucible opening, so that the peeled crystal layer caused by the excessive crystallization will fall into the silicon melt, thereby causing the risk of dislocation to increase.
[0068] In addition, the length of crystallization (crystal growth) can be obtained as the longest distance from the starting point of crystallization to the outermost periphery of the crystallized region. Alternatively, it can be obtained as the difference ΔB=B2-B1 between the boundary position B1 between the coated region and the uncoated region of the crystallization accelerator and the boundary position B2 between the crystallized region and the non-crystallized region after heat treatment.
[0069] The barium concentration in the crystal layer formed on the inner surface 10i of the crucible base 10 after the heat treatment is preferably less than 1 ppm. In this way, by crystallizing the inner surface 10i of the crucible base 10 without using a large amount of crystallization accelerator, crystallization in the in-plane direction of the crucible can be promoted, and a thin crystal layer can be uniformly formed on the inner surface 10i of the crucible base 10.
[0070] The quartz glass crucible 1 of the present embodiment can be manufactured by manufacturing the crucible base 10 by a so-called rotational molding method and then applying a crystallization accelerator to the inner surface 10 i of the crucible base 10 .
[0071] Figure 4 Schematic diagram showing a method for producing a quartz glass crucible by rotational molding.
[0072] like Figure 4As shown, in the rotational molding method, a carbon mold 14 having a cavity matching the shape of a crucible is prepared, and natural quartz powder 16a and synthetic quartz powder 16b are sequentially filled along the inner surface 14i of the rotating carbon mold 14, thereby forming a raw quartz powder accumulation layer 16. The raw quartz powder adheres to the inner surface 14i of the carbon mold 14 due to centrifugal force, and stays at a certain position in this state, maintaining the shape of a crucible.
[0073] Next, an arc electrode 15 is placed in the carbon mold 14 to arc melt the raw quartz powder accumulation layer 16 from the inside of the carbon mold 14. Specific conditions such as heating time and heating temperature can be appropriately determined in consideration of the characteristics of the raw quartz powder and the size of the crucible.
[0074] During the arc melting process, the amount of bubbles in the fused silica glass is controlled by vacuuming the raw silica powder accumulation layer 16 through a plurality of vent holes 14a provided on the inner surface 14i of the carbon mold 14. Specifically, at the start of arc melting, the raw silica powder accumulation layer 16 is vacuumed to form the transparent layer 11, and after the transparent layer 11 is formed, the vacuuming of the raw silica powder is stopped or the suction force is weakened to form the bubble layer 12.
[0075] The arc heat is transferred from the inside to the outside of the raw silica powder accumulation layer 16, causing the raw silica powder to gradually melt. Therefore, by changing the decompression conditions at the time when the raw silica powder starts to melt, the transparent layer 11 and the bubble layer 12 can be formed separately. That is, if the decompression melting is performed to increase the decompression at the time when the raw silica powder melts, the atmospheric gas will not be sealed in the glass, so the fused silica becomes a silica glass containing no bubbles. In addition, if the normal melting (atmospheric pressure melting) is performed to reduce the decompression at the time when the raw silica powder melts, the atmospheric gas will be sealed in the glass, so the fused silica becomes a silica glass containing a plurality of bubbles.
[0076] Since the Fe and Ca concentrations on the inner surface 10i side of the crucible base 10 are higher than the Al concentration, low-output arc melting is performed for a long time at the end of the arc melting process. The Fe and Ca concentrations on the inner surface 10i of the crucible base 10 tend to increase as the low-output arc melting time increases. If the low-output arc melting time is too short, the Fe and Ca concentrations on the inner surface 10i will not change. If it is too long, the impurity concentration on the inner surface 10i will become excessively high, so it is necessary to set it to an appropriate time.
[0077] After that, the arc melting is terminated and the crucible is cooled. In the above manner, the crucible base 10 having the transparent layer 11 and the bubble layer 12 arranged in sequence from the inside to the outside of the crucible wall is completed. In this way, the crucible base 10 based on the present embodiment can be manufactured as follows: after the natural quartz powder 16a as the outer layer raw material is filled in the rotating carbon mold 14, the synthetic quartz powder 16b as the inner layer raw material is filled, and the raw quartz powder accumulation layer 16 is melted by arc.
[0078] Next, the crucible base 10 is shaped by cutting the edge and then cleaned with a cleaning solution and further rinsed with pure water. The cleaning solution is preferably prepared by diluting semiconductor-grade or higher hydrofluoric acid with pure water having a TOC of ≤ 2 ppb to 10 to 40 w%.
[0079] Next, a crystallization accelerator is applied to the inner surface 10i of the crucible base 10. The coating liquid is preferably applied using a brush. In order to evenly disperse the crystallization accelerator on the inner surface 10i, it is preferred to use a coating liquid prepared by dissolving the crystallization accelerator in pure water (15 to 25°C, 17.2 MΩ or more, TOC ≤ 2ppb). In order to increase the solubility of the crystallization accelerator, it is preferred to use a stirrer to stir the coating liquid.
[0080] Figure 5 This is a diagram for explaining a method for producing a silicon single crystal (single crystal pulling step) using a quartz glass crucible according to the present embodiment, and is a schematic cross-sectional view showing the structure of a single crystal pulling apparatus.
[0081] like Figure 5 As shown, a single crystal pulling device 20 is used in a pulling process of single crystal silicon based on the CZ method. The single crystal pulling device 20 includes a water-cooled chamber 21, a quartz glass crucible 1 for holding a silicon melt in the chamber 21, a carbon susceptor 22 for holding the quartz glass crucible 1, a rotating shaft 23 for supporting the carbon susceptor 22 rotatably and elevatingably, an axis driving mechanism 24 for rotating and elevating the rotating shaft 23, a heater 25 arranged around the carbon susceptor 22, a single crystal pulling wire 28 arranged above the quartz glass crucible 1 and on the same axis as the rotating shaft 23, and a wire winding mechanism 29 arranged above the chamber 21.
[0082] The chamber 21 is composed of a main chamber 21a and an elongated cylindrical crystal pulling chamber 21b connected to the upper opening of the main chamber 21a, and the quartz glass crucible 1, the carbon susceptor 22 and the heater 25 are arranged in the main chamber 21a. A gas inlet 21c for introducing an inert gas (purge gas) such as argon or a dopant gas into the main chamber 21a is arranged at the upper part of the crystal pulling chamber 21b, and a gas exhaust port 21d for exhausting the atmosphere gas in the main chamber 21a is arranged at the lower part of the main chamber 21a.
[0083] The carbon susceptor 22 is used to maintain the shape of the quartz glass crucible 1 softened at high temperature, and holds the quartz glass crucible 1 in a manner of covering it. The quartz glass crucible 1 and the carbon susceptor 22 constitute a crucible of a double structure that supports silicon melt in the chamber 21.
[0084] The carbon susceptor 22 is fixed to the upper end of the rotating shaft 23 , and the lower end of the rotating shaft 23 is connected to a shaft driving mechanism 24 that penetrates the bottom of the chamber 21 and is provided outside the chamber 21 .
[0085] The heater 25 is used to melt the polycrystalline silicon raw material filled in the quartz glass crucible 1 to generate the silicon melt 3 and to maintain the molten state of the silicon melt 3. The heater 25 is a resistance heating carbon heater and is provided so as to surround the quartz glass crucible 1 in the carbon susceptor 22.
[0086] As the silicon single crystal 2 grows, the amount of the silicon melt 3 in the quartz glass crucible 1 decreases, but the quartz glass crucible 1 rises so that the height of the melt surface remains constant.
[0087] The wire winding mechanism 29 is disposed above the crystal pulling chamber 21b, and the wire 28 extends downward from the wire winding mechanism 29 through the crystal pulling chamber 21b, and the front end of the wire 28 reaches the internal space of the main chamber 21a. The figure shows a state in which the single crystal silicon 2 is suspended on the wire 28 during the growth process. When the single crystal silicon 2 is pulled, the quartz glass crucible 1 and the single crystal silicon 2 are rotated separately, and the wire 28 is slowly pulled to grow the single crystal silicon 2.
[0088] In the single crystal pulling process, the inner surface of the crucible is crystallized, but due to the effect of the crystallization accelerator, the crystallization of the inner surface of the crucible is carried out uniformly, so that the dislocation of the single crystal silicon due to the peeling of the brown ring can be prevented. In addition, the quartz glass crucible 1 is softened, but the crystallization of the inner surface of the crucible is carried out uniformly, so that the strength of the crucible can be ensured and deformation can be suppressed. Therefore, it is possible to prevent the contact with the internal components of the furnace due to the deformation of the crucible and the change in the liquid level position of the silicon melt 3 due to the change in the volume of the crucible.
[0089] As described above, the quartz glass crucible 1 of the present embodiment includes the crucible base 10 made of silica glass and the coating film 13 containing the crystallization accelerator formed on the inner surface 10i of the crucible base 10. The concentration of Al contained in the depth region D1 from the inner surface 10i of the crucible base 10 to at least 0.5 mm is lower than the concentration of Fe, Ca, etc. contained in the depth region D1. Since the crystallization rate in the in-plane direction is faster than the crystallization rate in the depth direction when the inner surface is crystallized at a high temperature in the crystal pulling process, even if the coating of the crystallization accelerator occurs unevenly on the inner surface 10i, the inner surface of the crucible can be finally set to a state covered with a uniform crystal surface, and the peeling of crystal grains can be prevented.
[0090] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above embodiments, and various changes can be made without departing from the gist of the present invention, and these are of course included in the scope of the present invention.
[0091] Examples
[0092] Four crucible substrates with different metal impurity concentrations on the inner surface were prepared. After applying a barium carbonate solution to a part of the inner surface of the crucible substrate using a brush, the crucible was broken into small pieces. Multiple crucible pieces without barium carbonate coating obtained from the same crucible substrate were used to perform metal impurity analysis in the depth direction from the inner surface of the crucible substrate. In the metal impurity analysis, after dissolving the silica glass at a certain depth from the inner surface of the crucible by wet etching, the etching solution was recovered, and the amount of metal impurities dissolved in the etching solution was measured by ICP-MS (Inductively Coupled Plasma-Mass Spectrometry).
[0093] In the determination of Fe, Ca, and Al in metal impurities, the depth region from the inner surface of the crucible substrate to 0.3 mm was set as the first measurement range, the depth region from 0.3 to 0.5 mm was set as the second measurement range, and the depth region from 0.5 to 0.7 mm was set as the third measurement range. The measurement results are shown in Tables 1 and 2.
[0094] [Table 1]
[0095]
[0096] As shown in Table 1, regarding the Fe and Al concentration distributions of the crucible substrate of Comparative Example 1, the Fe concentration was low in the entire region in the depth direction from the inner surface to 0.7 mm, and the relationship of Fe concentration < Al concentration was established. And, regarding the Fe and Al concentration distributions of the crucible substrate of Comparative Example 2, the relationship of Fe concentration > Al concentration was established in the depth region from the inner surface to 0.3 mm, and the relationship of Fe concentration < Al concentration was established in the depth region from 0.3 to 0.7 mm. In contrast, regarding the Fe and Al concentration distributions of the crucible substrate of Example 1, the relationship of Fe concentration > Al concentration was established in the depth region from the inner surface to 0.5 mm, and the relationship of Fe concentration < Al concentration was established in the depth region from 0.5 to 0.7 mm. Moreover, in the crucible substrate of Example 2, the relationship of Fe concentration > Al concentration was established in the entire region in the depth direction from the inner surface to 0.7 mm.
[0097] [Table 2]
[0098]
[0099] As shown in Table 2, the Ca concentration distribution also tends to be the same as that of Fe. That is, regarding the Ca and Al concentration distributions of the crucible substrate in Comparative Example 1, the Ca concentration is low in the entire region in the depth direction from the inner surface to 0.7 mm, and the relationship of Ca concentration < Al concentration holds. And regarding the Ca and Al concentration distributions of the crucible substrate in Comparative Example 2, the relationship of Ca concentration > Al concentration holds in the depth region from the inner surface to 0.3 mm, and the relationship of Ca concentration < Al concentration holds in the depth region from 0.3 to 0.7 mm. In contrast, regarding the Ca and Al concentration distributions of the crucible substrate in Example 1, the relationship of Ca concentration > Al concentration holds in the depth region from the inner surface to 0.5 mm, and the relationship of Ca concentration < Al concentration holds in the depth region from 0.5 to 0.7 mm. Moreover, in the crucible substrate of Example 2, the relationship of Ca concentration > Al concentration holds in the entire region in the depth direction from the inner surface to 0.7 mm.
[0100] As described above, in the crucible samples of Comparative Examples 1 and 2, the Fe concentration and Ca concentration in the depth region from the inner surface to 0.5 mm are lower than the Al concentration. In contrast, in the crucible samples of Examples 1 and 2, the Al concentration in the depth region from the inner surface to 0.5 mm is lower than the Fe concentration and Ca concentration.
[0101] In the determination of B, Mg, and Cr among metal impurities, the depth region from the inner surface to 1.0 mm is set as the first measurement range, the depth region from 1.0 to 2.0 mm is set as the second measurement range, the depth region from 2.0 to 3.0 mm is set as the third measurement range, the depth region from 3.0 to 4.0 mm is set as the fourth measurement range, and the depth region from 4.0 to 5.0 mm is set as the fifth measurement range. The measurement results are shown in Tables 3 to 5.
[0102] [Table 3]
[0103]
[0104] As shown in Table 3, regarding the B concentration distribution of the crucible base of Comparative Example 1, the B concentration in the entire region from the inner surface to the depth direction of 5 mm or less is 0.1 ppm. Regarding the B concentration distribution of the crucible base of Comparative Example 2, although the B concentration in the depth region from the inner surface to 1 mm is 0.01 ppm, the B concentration distribution in the depth region from 1 to 5 mm is 0.1 ppm. Regarding the B concentration distribution of the crucible base of Example 1, although the B concentration in the depth region from the inner surface to 2 mm is 0.02 ppm or less, the B concentration distribution in the depth region from 2 to 5 mm is 0.1 ppm. Regarding the B concentration distribution of the crucible base of Example 2, although the B concentration in the depth region from the inner surface to 3 mm is 0.02 ppm or less, the B concentration distribution in the depth region from 3 to 5 mm is 0.1 ppm.
[0105] [Table 4]
[0106]
[0107] As shown in Table 4, regarding the Mg concentration distribution of the crucible base of Comparative Example 1, the Mg concentration in the entire region from the inner surface to the depth direction of 5 mm or less is 0.14 ppm. Regarding the Mg concentration distribution of the crucible base of Comparative Example 2, although the Mg concentration in the depth region from the inner surface to 1 mm is 0.01 ppm, the Mg concentration distribution in the depth region from 1 to 5 mm is 0.14 ppm. Regarding the Mg concentration distribution of the crucible base of Example 1, although the Mg concentration in the depth region from the inner surface to 2 mm is 0.01 ppm or less, the Mg concentration distribution in the depth region from 2 to 5 mm is 0.14 ppm. Regarding the Mg concentration distribution of the crucible base of Example 2, although the Mg concentration in the depth region from the inner surface to 3 mm is 0.01 ppm or less, the Mg concentration distribution in the depth region from 3 to 5 mm is 0.14 ppm.
[0108] [Table 5]
[0109]
[0110] As shown in Table 5, regarding the Cr concentration distribution of the crucible base of Comparative Example 1, the Cr concentration in the entire region from the inner surface to the depth direction of 5 mm or less is 0.08 ppm. Regarding the Cr concentration distribution of the crucible base of Comparative Example 2, although the Cr concentration in the depth region from the inner surface to 1 mm is 0.01 ppm, the Cr concentration distribution in the depth region from 1 to 5 mm is 0.08 ppm. Regarding the Cr concentration distribution of the crucible base of Example 1, although the Cr concentration in the depth region from the inner surface to 2 mm is 0.02 ppm or less, the Cr concentration distribution in the depth region from 2 to 5 mm is 0.08 ppm. Regarding the Cr concentration distribution of the crucible base of Example 2, although the Cr concentration in the depth region from the inner surface to 3 mm is 0.02 ppm or less, the Cr concentration distribution in the depth region from 3 to 5 mm is 0.08 ppm.
[0111] As described above, in the crucible samples of Comparative Examples 1 and 2, the maximum value of the B concentration in the depth region from the inner surface to 2.0 mm is equal to the maximum value of the B concentration in the depth region from 2.0 to 5.0 mm from the inner surface, whereas in the crucible samples of Examples 1 and 2, the maximum value of the B concentration in the depth region of 2.0 mm or less from the inner surface is lower than the maximum value of the B concentration in the depth region from 2.0 to 5.0 mm from the inner surface. The same tendency is observed for Mg and Cr.
[0112] Next, a heating test was conducted using a crucible piece coated with barium carbonate. In the heating test, a crucible piece with a side of 10 to 20 cm, an area of 200 cm2 or more, and an aspect ratio as close to 1 as possible was used. Regarding the heating conditions, the temperature was raised from room temperature to 1580°C in a furnace in an Ar atmosphere over 2.5 hours, and then maintained at 1580°C for 10 hours. The pressure in the furnace maintained at 1580°C was 20 Torr.
[0113] Afterwards, the crystallization state of the inner surface of the crucible substrate was evaluated. Specifically, the crystallization rate in the in-plane direction and the crystallization rate in the depth direction were respectively calculated from the width and thickness of the crystal layer on the inner surface of the crucible substrate, and the presence or absence of crystallization unevenness was further confirmed by visual inspection. Here, the crystallization rate in the in-plane direction is the value of the crystallization length in the in-plane direction divided by the time maintained at a high temperature of 1580°C, that is, 10 hours. Similarly, the crystallization rate in the depth direction is the value of the crystallization length in the depth direction divided by 10 hours. The crystallization length in the in-plane direction is the maximum distance from the starting point of crystallization to the extension of the crystal layer. In addition, the crystallization length in the depth direction is the maximum thickness of the crystal layer of the cross section of the cut sample. The so-called crystallization unevenness refers to the fact that there are parts on the inner surface of the crucible substrate that are not devitrified and maintained as glass in the coating range of barium carbonate, especially an area of more than 5% that is not devitrified.
[0114] As shown in Tables 1 to 5, the results show that in the crucible samples of Comparative Examples 1 and 2, uneven crystallization was observed on the inner surface, but in the crucible samples of Examples 1 and 2, uneven crystallization was not observed on the inner surface and the entire surface was uniformly crystallized. The ratio of the crystallization rate in the in-plane direction to the crystallization rate in the depth direction of each crucible sample was calculated, and the results were 0.5 for Comparative Example 1, 1 for Comparative Example 2, 1.5 for Example 1, and 100 for Example 2. From the above results, it can be seen that if the ratio of the crystallization rate is 1.5, the inner surface of the crucible can be uniformly crystallized.
[0115] Description of Reference Numerals
[0116] 1-quartz glass crucible, 2-single crystal silicon, 3-silicon melt, 10-crucible base, 10a-side wall, 10b-bottom, 10c-corner, 10i-inner surface, 11-transparent layer, 12-bubble layer, 13-coating film containing crystallization promoter, 14-carbon mold, 14a-vent, 14i-inner surface of carbon mold, 15-arc electrode, 16-raw material quartz powder accumulation layer, 16a-natural quartz powder, 16b-synthetic quartz powder, 20-single crystal pulling device, 21-chamber, 21a-main chamber, 21b-crystal pulling chamber, 21c-gas inlet, 21d-gas outlet, 22-carbon base, 23-rotating axis, 24-axis driving mechanism, 25-heater, 28-crystal pulling wire, 29-winding mechanism.
Claims
1. A quartz glass crucible, which is a quartz glass crucible for pulling single crystal silicon, characterized in that: have: a crucible substrate comprising silica glass; and A coating film containing a crystallization accelerator is formed on the inner surface of the crucible base. The Fe concentration in a first depth region at least 0.5 mm or less from the inner surface is higher than the Al concentration in the first depth region.
2. The quartz glass crucible according to claim 1, wherein: The Ca concentration contained in the first depth region is higher than the Al concentration contained in the first depth region.
3. The quartz glass crucible according to claim 1, wherein: The concentration of B contained in a second depth region of 2 mm or less from the inner surface is lower than the concentration of B contained in a third depth region of 2 mm to 5 mm or less from the inner surface.
4. The quartz glass crucible according to claim 3, wherein: The Mg concentration contained in the second depth region is lower than the Mg concentration contained in the third depth region.
5. The quartz glass crucible according to claim 3, wherein: The Cr concentration in the second depth region is lower than the Cr concentration in the third depth region.
6. The quartz glass crucible according to claim 1, wherein: The concentration of the crystallization accelerator in the coating film containing the crystallization accelerator is 1.0×10 12 ~2.6×10 15 atoms / cm2.
7. The quartz glass crucible according to claim 1, wherein: When the heat treatment is performed at 1580° C., a ratio of a crystallization rate in the in-plane direction of the inner surface to a crystallization rate in the depth direction is 1.5 to 400.
8. The quartz glass crucible according to claim 7, wherein: The heating time from room temperature to 1580° C. for the heat treatment is 2.5 hours, the holding time at 1580° C. is 10 hours, and the gas pressure during the heat treatment is 20 Torr.
9. The quartz glass crucible according to claim 8, wherein: The length of the in-plane direction of the crystallization extended on the inner surface after the heat treatment is 1 mm to 60 mm.
10. The quartz glass crucible according to claim 7, wherein: The crystallization accelerator contained in the coating film containing the crystallization accelerator is Ba, and the Ba concentration in the crystal layer formed after the heat treatment is less than 1 ppm.
11. The quartz glass crucible according to claim 1, wherein: The crucible base has a cylindrical side wall portion, a bottom portion, and a corner portion disposed between the side wall portion and the bottom portion. In the inner surface of the crucible base, the area near the edge from the upper end of the edge to at least 20 mm below is an area not coated with a crystallization promoter. The coating film containing the crystallization accelerator is formed on the entire inner surface except for the uncoated area.
12. A method for producing single crystal silicon, characterized in that: A silicon single crystal is pulled using the quartz glass crucible according to any one of claims 1 to 11.
Citation Information
Patent Citations
Surface-treated crucible for improved dislocation-free performance
JP1997110590A
Silica vessel
JP2012211082A
Method of impurity analysis of quartz crucible and impurity recovery jig used for the same
JP2019066262A
Devitrification agent for quartz glass crucible crystal growth method
JP2019509969A
Method for manufacturing silicon single crystal
JP2020200236A